2007
DOI: 10.1213/01.ane.0000260563.39299.9c
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Local Anesthetic Infusion as a Treatment for Complex Regional Pain Syndrome in a Child

Abstract: Diagnosis and treatment of complex regional pain syndrome in children is one of the most challenging clinical pain problems encountered in the chronic pain setting. Despite the intense and debilitating nature of the pain, referral to appropriate specialists often comes too late, thereby prolonging an already arduous (and controversial) course of treatment and risking long-term disability. On the contrary, full recovery can be expected with early diagnosis and prompt treatment. The following case study describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
0
8
0
4
Order By: Relevance
“…The literature search uncovered one case report of the use of IT lidocaine in the treatment of chronic pain (179). A 28‐year‐old woman with spastic diplegia and severe neuropathic and somatic pain had spasticity scores on the Ashworth and Tardieu scales of 4 and 5, respectively, and a VAS pain score of 10 out of 10.…”
Section: Supporting Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search uncovered one case report of the use of IT lidocaine in the treatment of chronic pain (179). A 28‐year‐old woman with spastic diplegia and severe neuropathic and somatic pain had spasticity scores on the Ashworth and Tardieu scales of 4 and 5, respectively, and a VAS pain score of 10 out of 10.…”
Section: Supporting Literature Reviewmentioning
confidence: 99%
“…Chronic Pain Management: Case Report Only one published case report has described the use of IT ropivacaine in the management of chronic pain. The report described an eight‐year‐old girl with CRPS and severe pain in both feet that began without any recalled trauma or inciting event (179). Epidural ropivacaine provided complete pain relief in the right foot but no change in pain in the left foot.…”
mentioning
confidence: 99%
“…Intrathecal drug delivery can be effective in treating pain states that are refractory to epidural analgesia . In the pediatric population, intrathecal infusions have been successfully utilized to treat severe cancer pain and CRPS I .…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal administration of both opioids and local anesthetics has been described in children . Farid and Heiner successfully treated an 8‐year‐old girl with chronic left foot pain by placing an intrathecal catheter at the L4‐5 spinal space and infusing 0.2% ropivacaine at 0.03 mg/kg/h for 1 week . Intrathecal clonidine administration, which is commonly performed in adults, has also been reported in a terminally ill child .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some of the best data for neuromodulation therapies for CRPS exist for targeted drug delivery. Using the same search paradigm as noted above, seven reports of IT baclofen (ITB) therapy for CRPS‐related dystonia, three reports of IT analgesics for CRPS‐related pain, six reports of ITDD for chronic pain patients including those with CRPS, three reports of alternate IT agents for CRPS‐related pain, one review paper, and one survey of CRPS treatment practices were identified .…”
Section: Intrathecal Drug Delivery (Itdd)mentioning
confidence: 99%